Clinico-hematological analysis of pancytopenia - Jella, Ramdas; Jella, Vasantha (International Journal of Advances in Medicine, 2017)
Background: Pancytopenia is a manifestation of a wide variety of disorders which primarily or secondarily affect the bone marrow. It is a relatively common condition whose causative factors may vary with different geographical locations. Thus, to determine the causative agents and the clinical symptoms is essential for the management of this condition. Methods: This study was conducted on 56 patients above the age of 18 years presenting with pancytopenia. All the patients were subjected to thorough clinical and physical examination. Blood samples were collected for complete blood analysis and biochemical tests and peripheral blood smear was taken. Urine and stool samples were also taken for occult blood analysis. Bone marrow aspiration and trephine biopsies were performed wherever necessary as per the clinical symptoms. Results: Out of the 56 patients, 58.9% were males and 41.1% were females. The mean age of the patients was 34.9±4.3 years. The major presentation of the patients with pancytopenia was megaloblastic anemia, in 42.9 of the cases, followed by aplastic anemia in 23.2% of the cases. Among the common clinical symptoms, the most common one was pallor (73.2%) followed by weight loss (62.5%) and dyspnea (51.8%). Conclusions: Megaloblastic anemia is the most common cause of pancytopenia followed by aplastic anemia, with pallor being the most common clinical symptom. Therefore, the clinical findings along with the hematological analysis along with bone marrow aspiration examination are very important for an early diagnosis of pancytopenia so that early intervention can be taken for the patient and enhance the survival rate. <span style="font-size: 11.0pt; line-height: 115%; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Pancytopenia, Megaloblastic anemia, Aplastic anemia